Young adults’ knowledge, attitudes, and practices regarding premarital screening for genetic blood disorders and associated sociodemographic determinants in the Ahafo Region of Ghana: a cross-sectional study - Sarpong, Ma. L.; Tetteh, Richard J.; Amponsah, Francis A.; Amo-Kodieh, Philip; Owusu, Evans A.; Ntiamoah, Paul; Pillay, Julian D.; Kuupiel, Desmond (Archives of public health = Archives belges de santé publique, 2025)
Background Hereditary diseases, particularly genetic blood disorders such as Sickle Cell Disease (SCD), Glucose-6-Phosphate Dehydrogenase (G6PD) deficiency, and Thalassemia, pose significant public health challenges. Premarital carrier screening (PMCS) is a critical preventive measure, yet its uptake remains low in many regions, including the Ahafo Region of Ghana. This study assessed young adults’ knowledge, attitudes, and practices (KAP) regarding PMCS for SCD, G6PD deficency, and Thalassemia and determined factors associated with these KAP outcomes in the Ahafo Region. Methods A cross-sectional study was conducted from January to March 2024, involving 460 young adults aged 18–35 years attending various health facilities in the Ahafo Region. Data were collected using a validated structured questionnaire, translated into the local dialect for clarity. The questionnaire covered socio-demographic information, knowledge of PMCS, attitudes towards PMCS, and PMCS practices. Data were analysed using Stata version 14, with descriptive statistics, Chi-square tests for associations, and logistic regression to identify significant predictors of KAP. Results The study population was predominantly female (85.7%), with a mean age of 24.7 years. Only 15.4% ( n = 71) of respondents demonstrated good knowledge of PMCS. Key factors influencing knowledge included female gender, age 26–35 years, tertiary education, and receiving information from healthcare services. Positive attitudes towards PMCS were observed in 66.7% of respondents, significantly associated with tertiary education, self-employment, unemployment, and cohabiting marital status. However, only 14.1% exhibited positive PMCS practices, with significant predictors being tertiary education and being married. These findings indicate a substantial gap between awareness and actual practice of PMCS. Conclusion This study underscores the urgent need for targeted educational interventions and policy measures to enhance PMCS uptake among young adults in the Ahafo Region. Improving healthcare communication, integrating PMCS education into tertiary curricula, addressing sociocultural barriers, and enacting supportive policies are essential steps. Engaging various stakeholders, including healthcare providers, educational institutions, community leaders, policymakers, and NGOs, is crucial for effectively translating positive attitudes into proactive practices and reducing the prevalence of genetic blood disorders in the Ahafo Region and Ghana as a whole.